Electrochemical performance of activated carbons prepared from rice husk in different types of non-aqueous electrolytes. (December 2015) - Kumagai, Seiji; Tashima, Daisuke
Abstract: Activated carbons (ACs) prepared from rice husk (RH), an agricultural byproduct, have mesoporosity that is obtainable from leaching of the mineral component of silica. To verify the suitability of RH-derived ACs for the use of electrode materials of electrical double-layer capacitors, we evaluated the electrochemical performance of three RH-derived ACs (two micro- and mesoporous ACs and one mesoporous AC). Evaluation was done by using the non-aqueous ionic electrolyte solutions 1 mol dm −3 triethylmethyl ammonium tetrafluoroborate/propylene carbonate (PC) solution, 1.5 mol dm −3 spiro-(1, 1′)-bipyrrolidinium tetrafluoroborate/PC (SBP·BF4 /PC) solution, and the ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIm·BF4 ). Under low voltage scan rate (1 mV s −1 ) and low current density (<1 mA cm −2 ), mesoporous AC, which had the highest specific surface area, showed the highest specific capacitance (120 F g −1 ) in EMIm·BF4 . However, its specific capacitance considerably decreased because of the increase in scan rate and current density. Under high scan rate (10 and 100 mV s −1 ) and high current density (>10 mA cm −2 ), micro- and mesoporous AC in 1.5 mol dm −3 SBP·BF4 /PC showed the highest specific capacitance and highest retention of specific capacitance, even though its specific surface area was not the highest. Mesoporous AC showed voltage-dependent specific capacitance, indicating that ionic transport in the mesoporous structure was sensitive to electric field. It was finally shown that micro- and mesoporosity developed by utilizing natural structure and composition of RH was useful for the electrode materials of advanced electrical double-layer capacitors requiring more viscous non-aqueous electrolytes. Graphical abstract: Highlights: The electrochemical performance of activated carbons from rice husk was evaluated. Two electrolytes based on propylene carbonate and an ionic liquid were used. Ion motions affected the electrochemical properties obtained with the ionic liquid. Micro- and mesoporous structures led to high capacitance in the electrolytes.